Characteristics of Patients in Receiving Informed Consent on Arteriovenous Shunt Vascular Access Measures in the Hemodialysis Room of Temanggung Hospital - Stefani Danik Kurniyati; Sodiq Kamal; Nurul Hidayah (Universitas Muhammadiyah Tangerang, 2022)
Background: Hemodialysis is a medical procedure that must be performed in patients with Chronic Kidney Disease (CKD). Infection and hematoma are the cause of the use of temporary access can be a vascath (percutaneous venous catheter) where the catheter is inserted into the large femoral vein. The importance of giving informed consent in patients with Chronic Kidney Disease (CKD) to install an Arteriovenous (AV) shunt vascular access to reduce infection and hematoma. Approval and rejection of medical treatment in patients are influenced by patient characteristics which include age, gender, education, occupation, attitude, knowledge and language. Objective: This study aims to determine the relationship between patient characteristics in receiving informed consent and AV shunt vascular access in the hemodialysis room. Methods: This study uses a quantitative method with a descriptive correlative design. This type of research is using a descriptive cross-sectional study approach. Sampling with a total sampling of 24 respondents. Results: The results showed that the relationship between characteristics such as education, knowledge and patient attitudes in receiving informed consent had an effect on Arteriovenous (AV) Shunt vascular access (p-value = 0.005). Conclusion: There is a relationship between the characteristics of patients in receiving informed consent and access to vascular Arteriovenous (AV) shunts in the hemodialysis room. Acceptance of informed consent for Arteriovenous (AV) shunt vascular access in the hemodialysis room, the results showed that most of the respondents did not agree to install Arteriovenous (AV) shunt vascular access as many as 18 respondents (75.0%). The recommendation from the main findings of this study is the importance of providing complete and clear information to patients about the informed consent of the ArterioVenous (AV) Shunt vascular access plan before hemodialysis.Keywords: Informed Consent; Vascular Access Arteriovenous (AV) Shunt; Hemodialysis